SISTEM MANAJEMEN PERGUDANGAN UNTUK MENINGKATKAN KEAKURATAN PENCATATAN STOCK BARANG PADA PERUSAHAAN RITEL DI JAKARTA - Tanisri, Roberta Heni Anggit (Inaque : Journal of Industrial and Quality Engineering, 2022)
JGT Retail is one of the companies engaged in retail located in the DKI Jakarta area. The problem that is often faced is related to the accuracy of the data on the recording of stock of goods in the system with the actual stock of goods. The improvement system is carried out by implementing a warehousing management system by designing a Standard Operating Procedure (SOP) for stock-taking activities. The proposal to make a stock-taking SOP is carried out in a period of every week. The accuracy of stock data between the system and the actual before the SOP Stock Opname was 85%. After the weekly stock-taking activity, the average accuracy of stock data between the system and the actuality increased to 97.7%.